Ocena przydatności finansowych mierników kreowania wartości w zarządzaniu przedsiębiorstwem : analiza porównawcza - Nita, Bartłomiej (Usefulness evaluation of financial value creation metrics in corporate management : the comparative analysis, 2006)
The paper presents the comparative study of several value creation metrics from the point of view of their usefulness in corporate management. The metrics that were taken into account in the analysis are: economic value added, market value added, shareholder value added, cash flow return on investment, total shareholder return and total business return. The metrics were compared in respect of the specified set of criteria including their ability to evaluate corporate performances, correlation with the total return to shareholders, treatment of metrics as the basis of an incentive compensation plan that encourages managers to think and act like owners and others. Some results of different empirical research and analysis are widely quoted in the article.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 284-303